2021
DOI: 10.1177/2050313x21990982
|View full text |Cite
|
Sign up to set email alerts
|

A familial case of CAMK2B mutation with variable expressivity

Abstract: Variants in CAMK2-associated genes have recently been implicated in neurodevelopmental disorders and intellectual disability. The clinical manifestations reported in patients with mutations in these genes include intellectual disability (ranging from mild to severe), global developmental delay, seizures, delayed speech, behavioral abnormalities, hypotonia, episodic ataxia, progressive cerebellar atrophy, visual impairments, and gastrointestinal issues. Phenotypic heterogeneity has been postulated. We present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…A heterozygous c.85C>T, p.(Arg29*) mutation in CAMK2B was found in a patient with mild ID, delayed speech development and seizures ( Küry et al, 2017 ). This mutation was also reported in a 3-year-old European girl with complex focal seizures and global neurodevelopmental delay ( Heiman et al, 2021 ). This maternally inherited pathogenic variant of the CAMK2B gene only mildly affected the patient’s sibling, with the same variant, while the mother was phenotypically healthy and intellectually normal ( Heiman et al, 2021 ).…”
Section: Functional Implications Of Ca 2+ /Calmodu...mentioning
confidence: 65%
See 2 more Smart Citations
“…A heterozygous c.85C>T, p.(Arg29*) mutation in CAMK2B was found in a patient with mild ID, delayed speech development and seizures ( Küry et al, 2017 ). This mutation was also reported in a 3-year-old European girl with complex focal seizures and global neurodevelopmental delay ( Heiman et al, 2021 ). This maternally inherited pathogenic variant of the CAMK2B gene only mildly affected the patient’s sibling, with the same variant, while the mother was phenotypically healthy and intellectually normal ( Heiman et al, 2021 ).…”
Section: Functional Implications Of Ca 2+ /Calmodu...mentioning
confidence: 65%
“…This mutation was also reported in a 3-year-old European girl with complex focal seizures and global neurodevelopmental delay ( Heiman et al, 2021 ). This maternally inherited pathogenic variant of the CAMK2B gene only mildly affected the patient’s sibling, with the same variant, while the mother was phenotypically healthy and intellectually normal ( Heiman et al, 2021 ). Similarly, a heterozygous c.416C>T, p.(Pro139Leu) variant of CAMK2B found in four Caucasian patients presented with severe ID, global developmental delay, hypotonia and microcephaly ( Küry et al, 2017 ), was also reported in a 22-year-old South Asian woman ( Rizzi et al, 2020 ) as well as in a MECP-2 (methyl-CpG binding protein 2) negative proband of Japanese origin ( Iwama et al, 2019 ).…”
Section: Functional Implications Of Ca 2+ /Calmodu...mentioning
confidence: 65%
See 1 more Smart Citation
“…The CDK13 and CAMK2B genes have been recently annotated OMIM genes, related to syndromic neurodevelopmental disorders (congenital heart defects, dysmorphic facial features, intellectual developmental disorder associated to MIM# 617360, mental retardation, and autosomal dominant 54 associated to MIM# 617799) [26][27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…CDK13 codes for a member of the cyclin-dependent serine/threonine protein kinase (STK) family, which phosphorylate targets, such as RNA polymerase II-involved in extracellular and growth signaling [33]. The majority of mutations in CDK13 are missense mutations, occurring within the protein kinase domain leading to significant loss of catalytic activity.…”
Section: Discussionmentioning
confidence: 99%